Thick Electrode Batteries: Principles, Opportunities, and Challenges. Issue 33 (24th July 2019) - Kuang, Yudi; Chen, Chaoji; Kirsch, Dylan; Hu, Liangbing
Abstract: The ever‐growing portable electronics and electric vehicle markets heavily influence the technological revolution of lithium batteries (LBs) toward higher energy densities for longer standby times or driving range. Thick electrode designs can substantially improve the electrode active material loading by minimizing the inactive component ratio at the device level, providing a great platform for enhancing the overall energy density of LBs. However, extensive efforts are still needed to address the challenges that accompany the increase in electrode thickness, not limited to sluggish charge kinetics and electrode mechanical instability. In this review, the principles and the recent developments in the fabrication of thick electrodes that focus on low‐tortuosity structural designs for rapid charge transport and integrated cell configuration for improved energy density, cell stability, and durability are summarized. Advanced thick electrode designs for application in emerging battery chemistries such as lithium metal electrodes, solid state electrolytes, and lithium–air batteries are also discussed with a perspective on their future opportunities and challenges. Finally, suggestions on the future directions of thick electrode battery development and research are suggested. Abstract : Thick electrode design is one of the most promising ways to improve battery energy density. In this contribution, the recent advances in the rational design of thick electrodes, with focus on the ion‐transfer kinetics and electrode mechanical robustness, as well as potential applications in emerging lithium battery chemistries are reviewed.